High sedimentation rates lead to rapid vegetation recovery in tidal brackish wetland restoration - van Proosdij, Danika; Graham, Jennie; Lemieux, Ben; Bowron, Tony; Poirier, Emma; Kickbush, Jocelyn; Ellis, Kirsten; Lundholm, Jeremy (Frontiers in Ecology and Evolution, 2023)
Tidal wetland restoration in the Bay of Fundy involves restoring tidal hydrology to sites with tidal restrictions. Most have focused on salt marsh sites close to the mouth of estuaries, but there are also many tidally restricted wetlands closer to the freshwater end of tidal rivers. Recovery of salt marsh vegetation has been rapid in past projects, but little is known about sediment and vegetation dynamics post restoration in tidal brackish or freshwater environments. We implemented tidal wetland restoration projects on two tidal rivers near the inland limit of saltwater. Hydrological restoration involved breaching (St. Croix) or realigning agricultural dykes (Belcher Street). We monitored hydrology, sediment accretion and vegetation at replicated plots on restoration sites and nearby reference tidal marshes; and conducted habitat mapping and elevation surveys using drones. After re-establishing tidal flow, sediment accretion was very rapid, leading to a deep layer of new sediments. Plant colonization at both sites resulted in a high diversity of halophytes in the first two years post restoration, but the St. Croix site transitioned to freshwater wetland species dominating by the fifth-year post-restoration. The Belcher St. site has a mix of freshwater and brackish wetland species after the fourth-year post-restoration. High suspended sediment concentrations at both sites suggest that each site was positioned closed to the estuarine turbidity maximum within its river. Tidal wetland restoration at the head of estuaries may benefit from the large ecological disturbance associated with rapid sediment accretion, providing a productive substrate with little competition from prior vegetation, but ultimate vegetation patterns may take longer to develop as elevation gains alter tidal flooding frequency. Low salinities suggest that the physical disturbance of sediment burying prior vegetation is the main mechanism creating a clean slate for plant recolonization, rather than mortality of terrestrial vegetation due to salt water. The majority of elevation change was due to allochthonous sediment deposition, with belowground processes playing a minor role. The wetlands restored showed substantial net elevation gains in the first years following tidal hydrological restoration, but long-term monitoring is required to track their overall resilience in the face of sea level rise.